Characterization of Batik Industrial Wastewater in Bogor City - Siti Kholisoh; Intan Wulandari; Ani Iryani; Sutanto Sutanto; Siti Warnasih (Helium: Journal of Science and Applied Chemistry, 2022)
Wastewater from the batik industry in Bogor City is the most waste produced from the dyeing process. The batik industry produces waste with concentrated color due to the high concentration of color content from the dyeing process. This affects water bodies as a direct disposal site for waste. Batik waste also has the potential to contain heavy metal compounds derived from the composition of dyes. This will have an impact on the disruption of the balance in the environment around the industry. Therefore, it is necessary to characterize batik wastewater to determine the pollutant content. This research aims to characterize the batik industry wastewater in the city of Bogor by measuring the levels of COD, BOD, TSS, pH, temperature, total chromium content, total phenol content, and sulfide content according to the parameters P.16/MENLKH/SETJEN /KUM.1/4/2019. The results showed the characteristics of the wastewater from the batik industry in Bogor City with levels of COD in dyeing waste at 797 mg/L and total waste at 52463 mg/L, BOD levels in dyeing waste at 431 mg/L, and total waste at 238 mg/L. TSS in the dyeing waste is 706.5 mg/L and the total waste is 3679 mg/L, the temperature in the dyeing waste is 26.9 °C and the total waste is 26.3°C, pH in staining waste at 1.62 and total waste at 6.82; the total chromium content in the staining waste was 2.62 mg/L and the total waste was 940.2 mg/L, the total phenol content and sulfide content in the dyeing waste and total waste was not detected. The characteristics of batik waste are not by the established quality standards, so there is a need for processing before the waste is discharged into the environment.